UNWANTED CONTINUITY/WANTED DISCONTINUITY. LITERARY ECHOES OF THE POLISH PEOPLE’S REPUBLIC DISCOURSE IN THE 3RD REPUBLIC REALITY MARKED WITH RESSENTIMENT OF AN OPPRESSED PERIPHERY - Gosk, Hanna (Porównania, 2014)
The text analyzes the traces of the Polish People’s Republic dominant discourse and its counter-discourse in contemporary Polish prose writing which maintain the foundational national narrative developed under partitions in the 19th c. Traces of both discourses are still present in works by authors of various ideological commitments and they are subject to a range of uses.